Pengaruh Kinerja Keuangan Terhadap Pertumbuhan Ekonomi Dengan Alokasi Belanja Modal Sebagai Variabel Intervening - Anisya Ayu L; Sri Rahayu; Junaidi (Magister Ilmu Akuntansi Universitas Jambi, 2020)
This study aimed to examine the effect of financial performance on economic growth with the allocation of capital expenditure as an intervening variable in District/City Governments in Jambi Province. The financial performance variables measured were the degree of fiscal decentralization, growth of PAD, effectiveness of PAD, financial efficiency and BUMD’s contribution. Data analyzed using path analysis with AMOS program were based on secondary data in the form of panel data sourced from district/city APBD datas in Jambi Province. The results showed that only the degree of fiscal decentralization, the effectiveness of PAD and financial efficiency had direct effect on the allocation of capital expenditure. In addition, only growth of PAD, effectiveness of PAD, financial efficiency and allocation of capital expenditures had direct effect on economic growth. The capital expenditure allocation variable only partially mediated the effect of the fiscal decentralization, PAD effectiveness and financial efficiency on economic growth. Keywords: Financial Performance, Capital Expenditure, Economic Growth.